Clinicopathological profile of paediatric vitellointestinal duct anomalies - Radhika Krishna, Othuluru Hema; Sriampur, Srinivas; Vani Padmaja, Gaddam Janardhan; Kota, Ramesh Reddy (Asian Journal of Medical Sciences, 2021)
Background: Vitellointestinal duct (VID) or Omphalomesenteric duct (OMD) is the embryonic connection between the yolk sac and the primitive midgut. Anomalies result from failure of the involution of the VID. Normally, it obliterates between the fifth and seventh weeks of fetal life. They include Meckel’s diverticulum (MD), fibrous band, fistula, sinus tract, cyst, and umbilical polyp. Symptomatic cases require surgical correction. They are characterised by different clinical presentations and histological appearances. This study gathers a single paediatric institutional experience of VID remnants, their demographic, clinical profile, varied histomorphology including the presence of ectopic tissues.Aims and Objectives: The objective of this study was to retrospectively review all the symptomatic cases of VID abnormalities at a tertiary pediatric referral hospital. The demographic profile, clinical presentation, and histopathology were reviewed and descriptively analyzed. We classified these anomalies based on embryology and histology. The findings of this study will provide insights to pathologists and treating clinicians less exposed to these rare lesions.Materials and Methods: Data was retrieved retrospectively from the pathology records of a tertiary paediatric referral institute for 3 years. Histological slides of VID anomalies were reviewed and a descriptive analysis of the findings was performed. A thorough review of the literature was also done on these very rare lesions and their findings compared to our results.Results: A total of 60 cases of VID anomalies were encountered during the study period. There was significant male preponderance. The most common age group at surgery was infancy. MD was the commonest VID anomaly. The least common was vitelline fistula and only a single case was encountered in the study period. Ectopic tissues were seen in 25% of the cases and included gastric and colonic mucosae and pancreatic tissue.Conclusion: The histopathology of VID anomalies provides an interesting diagnostic experience for the reporting pathologist. Awareness of the embryology, presentation and histology of these lesions aids in accurate diagnosis.